2020
DOI: 10.1038/s41598-020-66617-2
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid channel regulates fibroblast differentiation and airway remodeling by modulating redox signals through NADPH Oxidase 4

Abstract: Asthma is characterized by pathological airway remodeling resulting from persistent myofibroblast activation. Although transforming growth factor beta 1 (TGFβ1), mechanical signals, and reactive oxygen species (ROS) are implicated in fibroblast differentiation, their integration is still elusive. We identified that Transient Receptor Potential Vanilloid 4 (TRPV4), a mechanosensitive ion channel mediates lung fibroblast (LF) differentiation and D. farinae-induced airway remodeling via a novel TRPV4-NADPH Oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In IPF models, Trpv4 –/– mice are protected from fibrosis 187 . TRPV4 modulates transforming growth factor (TGF)-β1-dependent actions in a SMAD -independent manner with enhanced actomyosin remodelling and increased nuclear translocation of the α-smooth muscle actin-transcription co-activator, myocardin-related transcription factor (MRTF)-A 188 , 189 . These data point to TRPV4 inhibition as a potential therapeutic approach in pulmonary fibrosis 189 .…”
Section: Respiratory Diseasementioning
confidence: 99%
“…In IPF models, Trpv4 –/– mice are protected from fibrosis 187 . TRPV4 modulates transforming growth factor (TGF)-β1-dependent actions in a SMAD -independent manner with enhanced actomyosin remodelling and increased nuclear translocation of the α-smooth muscle actin-transcription co-activator, myocardin-related transcription factor (MRTF)-A 188 , 189 . These data point to TRPV4 inhibition as a potential therapeutic approach in pulmonary fibrosis 189 .…”
Section: Respiratory Diseasementioning
confidence: 99%
“…Although the exact reason for the requirement of different PI3K isoforms in these studies is not clear, it could be due to different fibroblast cells used. Furthermore, recent studies from Paruchuri and colleagues demonstrated a critical role for NOX4 and reactive oxygen species (ROS) in TRPV4-mediated TGF-β1 induced lung fibroblast differentiation and D. farina-induced airway remodeling [83]. Specifically, NOX4 was shown to regulate TGF-β1-induced fibroblast differentiation via the activation of MRTF-A and increased PAI-1 expression, suggesting that NOX4 regulates fibrotic gene expression and matrix remodeling.…”
Section: Role Of Trpv4 Mechanotransduction In Pulmonary Fibrosismentioning
confidence: 99%
“…Specifically, NOX4 was shown to regulate TGF-β1-induced fibroblast differentiation via the activation of MRTF-A and increased PAI-1 expression, suggesting that NOX4 regulates fibrotic gene expression and matrix remodeling. Interestingly, the inhibition of NOX4 activity did not change TRPV4 activity, suggesting that NOX4 is downstream of TRPV4 [83]. Fibroblast differentiation can also be modulated by nitric oxide (NO) [84,85].…”
Section: Role Of Trpv4 Mechanotransduction In Pulmonary Fibrosismentioning
confidence: 99%
“…Mechanistically, TRPV4 regulates the pro-fibrotic functions of TGFb by modulating signaling pathways downstream of this cytokine, including activation of Phosphoinositide 3 kinase (PI3K)/Protein kinase B (AKT), MAPK/ERK, Rho/Rho kinase, NADPH oxidase 4 (NOX4), Myocardin-related transcription factor A (MRTF-A), and YAP/TAZ (Fig. 2) [136,144,146]. Importantly, pharmacological activation of TRPV4 can upregulate the expression of a-SMA and matrix molecules, formation of aligned collagen, phosphorylation of AKT, and activation of MRTF-A independently from TGFb [2,4,147].…”
Section: Trpv4 In Ecm Remodelingmentioning
confidence: 99%